1985
DOI: 10.1148/radiology.154.1.3964951
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the hook of hamate: radiographic signs.

Abstract: Isolated fractures of the hamulus, formerly considered rare, are being seen more frequently. Many of these injuries are sports related, particularly in golf, tennis, racquetball and baseball players. Failure to make an early diagnosis can result in severe pain and sometimes incapacitating disability. We studied the clinical and radiological findings in 12 patients who had fracture of the hook of the hamate. We propose three radiographic signs of fracture that are readily seen on routine PA projections: "absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 1 publication
(1 reference statement)
1
25
1
1
Order By: Relevance
“…The diagnosis may often be delayed because the signs and symptoms are rather non-specific, and routine radiography is not always diagnostic ( Norman et al 1985, Polivy et al 1985. In our series also, the diagnosis was delayed in 5 cases and routine radiography was diagnostic in only 1 case.…”
Section: Discussionmentioning
confidence: 53%
“…The diagnosis may often be delayed because the signs and symptoms are rather non-specific, and routine radiography is not always diagnostic ( Norman et al 1985, Polivy et al 1985. In our series also, the diagnosis was delayed in 5 cases and routine radiography was diagnostic in only 1 case.…”
Section: Discussionmentioning
confidence: 53%
“…To our knowledge, only one case of bilateral absence of the hook is reported in the literature by Seeger et al [21]; it was observed on plain radiographs. The hook is normally visualised in its full length on the carpal tunnel standard view [6], or more optimally on computed tomography [3,16] or magnetic resonance axial images (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Coupe axiale bilaterale en FFE montrant I' a. medi ane intracarpienne 11 gauche (fleche). Le vaisseau aberrant emet un hypersignal semblable 11 celui de l'a, ulnaire tflechesi and amyloidosis [16]. The deposited amyloid inside the carpal tunnel can erode and destroy the hamulus [16], as other carpal bones can be affected as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated fractures of the hamate hook appear to occur more frequently than previously reported, which could be attributed to the increasing popularity of sports activities, such as golf, tennis, baseball, and hockey, more careful assessment of wrist injuries, and improved radiographic imaging [1][2][3][4][5]. Hook fractures are caused by direct or indirect trauma or a combination of both.…”
Section: Introductionmentioning
confidence: 98%